Selenium-Based Drug Development for Antioxidant and Anticancer Activity - Sashi Debnath; Abhijeet Agarwal; Neha R. Kumar; Anjan Bedi (MDPI AG, 2022)
Selenium is one of the eight necessary trace elements humans require for active health balance. It contributes in several ways to the proper functioning of selenoprotein. Selenium has received enormous interest recently due to its therapeutic potential against a number of ailments. To date, numerous chemical compounds containing selenium have been investigated for the therapy of cancer and other disorders. Unifying the selenium atom into chemical components (typically organic) greatly increased their bioactivities. We foresee that the structure-property relationship of recently developed materials could significantly decrease the laborious work of background research to achieve target-oriented drug design in coming years. This review summarizes the research progress in the last 10 to 15 years and the application of selenium-containing compounds in the design and synthesis of those materials for potential antioxidant and anticancer agents.